Synchronization of the Transfer of the Indonesian State Capital According to Law Number 3 of 2022 Concerning the State Capital with the 1945 Constitution and Applicable Positive Laws - Ferdinand Nicholas (Asian Journal of Social and Humanities, 2023)
Until now, the capital city of Indonesia is the Special Capital Region of Jakarta (DKI Jakarta). Jakarta as the capital is the center of everything that makes Jakarta a big burden as the capital of Indonesia. President Joko Widodo moved the capital from Jakarta to Kalimantan under the name "Nusantara" as a form of representation of Indonesia's development. Law Number 3 of 2022 concerning State Capitals (UU IKN) was created, on January 18, 2022. However, this law experienced various problems due to the haste to ratify the IKN Law. The IKN Law is inconsistent with the 1945 Constitution and laws that are equivalent to the IKN Law do not involve the community's right to participate and obtain information from the government as their responsibility. As a result of the problems experienced in the UU IKN, this law must be corrected in detail and completely so that the UU IKN gets legal certainty and the IKN development process goes according to the goals of the state and nation. By considering every voice of the Indonesian people which is their right to build a prosperous country